Insights into the response of Miscanthus x giganteus to rhizobacteria: enhancement of metal tolerance and root development under heavy metal stress - Pešić, Mila; Radović, Svetlana; Rakić, Tamara; Dželetović, Željko; Stanković, Slaviša; Lozo, Jelena (Archives of Biological Sciences, 2024)
This article has been corrected. Link to the correction 10.2298/ABS240718021E Paper description: Rhizobacteria enhance the phytoremediation potential of Miscanthus x giganteus by stimulating growth and root development, resulting in increased biomass production, improved nutrient status, metal uptake, and accumulation. Transcriptomic analysis: rhizobacteria and x giganteus interaction modulates gene expression in roots, 9892 differential gene expression units DEGs change expression after treatment. Gene ontology analysis: upregulated DEGs enriched in 32 terms; downregulated genes enriched in 63 terms. Expression of MATE 40 and COBRA-like 1 (involved in plant response to biotic and abiotic stress, cell wall organization and cellular elongation processes, respectively) increased in bacteria-treated plants. Abstract: The use of bioenergy crops such as Miscanthus x giganteus in phytoremediation could have both environmental and economic benefits, such as biomass production and soil conservation for crops. In our previous work, we showed that rhizobacteria from the rhizosphere of M. x giganteus stimulated metal extraction and uptake and enhanced the phytoremediation ability of treated M. x giganteus. In the present study, we conducted transcriptome analysis and qPCR to elucidate the molecular mechanisms underlying these interactions in response to bacterial treatment by identifying the candidate genes involved in growth and development processes and metal uptake. Using high-throughput RNA sequencing of root samples, we found that 5134 and 4758 genes were up- and downregulated in plants treated with the rhizobacteria consortium. Gene ontology analysis showed that the upregulated DEGs were significantly enriched in 32 terms, while the downregulated genes were significantly enriched in 63 terms. Our results confirmed the increased expression of two genes: the multidrug and toxic compound extrusion, also known as multi-antimicrobial extrusion (MATE) 40, known for its role in plant response to biotic and abiotic stress, and COBRA-like protein 1 belonging to the COBRA-like (COBL) gene family, which encodes a putative glycosylphosphatidylinositol (GPI)-anchored protein involved in cell wall thickening, cell elongation, and biomass increase when compared to untreated plants. We present the first insight into a mechanism whereby the interaction between the rhizobacterial consortium and M. x giganteus fosters plant growth and enhances its capacity for phytoremediation.